Comparative Efficacy of Elsa and English Speaking Practice: A Quasi-Experimental Study on EFL Learning Outcomes - Arbain; Widi Syahtia Pane; Raodah Mifdtahul Jannah (Universitas Sulawesi Barat, 2023)
In an era where digital learning tools are reshaping the educational landscape, selecting the right language learning application becomes paramount, especially for institutions aiming to enhance their students' English proficiency. While numerous language applications exist, only a few are accessible without cost. This study zeroes in on two such free applications: ELSA and English Speaking Practice. The choice of these apps aimed to discern the instructional differences and their subsequent impact on learners. Conducted at SMK Negeri 17 Samarinda, the research involved two experimental classes: X Pharmacy 4 (33 students) and X Medical Laboratory Technology 1 (34 students). Using a Quasi-Experimental design, the study employed quantitative methods, including pre-test and post-test evaluations, to gauge the comparative effectiveness of the apps. The results were illuminating: the class utilizing ELSA witnessed a proficiency uptick of 15.21%, whereas the English Speaking Practice class observed a 13% increase. With a p-value of 0.000 <0.05, the data conclusively shows significant disparities in the efficacy of the two applications. This research underscores the importance of judiciously selecting digital tools in EFL contexts, ensuring optimal learning outcomes.